2022
DOI: 10.1136/annrheumdis-2022-eular.1175
|View full text |Cite
|
Sign up to set email alerts
|

Pos0180 the Efficacy and Safety of a Fixed-Dose Combination of Apocynin and Paeonol in Symptomatic Knee Oa: A Double-Blind, Randomized, Placebo-Controlled Clinical Trial

Abstract: BackgroundThere is a great unmet need for the development of effective treatments to treat the symptoms of OA. Nuclear-Factor Kappa-B (NF-κB) and Nrf2 play a key roles in OA pathogenesis and have been identified as potential targets. A fixed-dose combination of apocynin and paenol in a ratio of 2:7 (APPA) has been shown to inhibit activation of NF-κB and upregulate Nrf2. [1]ObjectivesWe report the results of a phase 2a study evaluating the efficacy and safety of APPA in patients with symptomatic knee OA.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Importantly, APPA has also been shown to provide effective pain relief in naturally occurring canine OA [ 41 , 42 ]. In addition, in a Phase 2a double blind placebo controlled study in subjects with knee OA, APPA provided pain relief in a subset of patients who experienced nociplastic/neuropathic pain [ 44 ]. These positive results from animals and humans reflect the findings presented here, i.e., that APPA has been shown to impact pathways known to be involved in the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, APPA has also been shown to provide effective pain relief in naturally occurring canine OA [ 41 , 42 ]. In addition, in a Phase 2a double blind placebo controlled study in subjects with knee OA, APPA provided pain relief in a subset of patients who experienced nociplastic/neuropathic pain [ 44 ]. These positive results from animals and humans reflect the findings presented here, i.e., that APPA has been shown to impact pathways known to be involved in the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 99%
“…APPA has been shown to provide pain relief in two studies in dogs with naturally occurring OA [ 40 , 41 ] and provided chondroprotection in the established rat meniscal tear model of OA [ 42 , 43 ]. In a recent Phase 2 trial, APPA was found to provide significant pain relief compared with placebo in a subset of patients with knee OA [ 44 ]. The combination of these compounds in APPA has potential to be an alternative to NSAIDs for managing the pain of OA and limiting disease progression.…”
Section: Introductionmentioning
confidence: 99%